Multiverse Analysis of Data from Preregistered Study - toward Preregistered Multiverse Analysis - Dominik Lenda; wolf vanpaemel (Open Science Framework, 2022)
We discussed the shortcomings of two crucial research practices which aim at reducing the influence of researcher degrees of freedom on statistical results, preregistration and multiverse analysis. We employed a multiverse analysis using data from a preregistered study, showing that preregistration may still hide arbitrariness in data processing. We argue that the best solution is to combine both, in a preregistered multiverse analysis.
This project is described in the poster which was presented at the 31st Annual Convention of Association for Psychological Science in Washington D.C. by Dominik Lenda.